Enlarged lymph node occupying the retroperitoneal space and psoas muscle causes ureteric compression and graft kidney hydronephrosis after COVID-19 mRNA vaccine booster: a case report - Dong Han Kim; Tae Hyun Ryu; Hee Yeoun Kim; Jeong Myung Ahn; Joon Seok Oh; Joong Kyung Kim (Clinical Transplantation and Research)
Vaccine-induced hypermetabolic lymph nodes have been clinically observed following coronavirus disease 2019 (COVID-19) mRNA vaccination. Specifically, the booster dose of the mRNA vaccines, produced by Pfizer and Moderna, has been linked to a relatively high incidence of lymphadenopathy. We present the case of a kidney transplant recipient who developed an enlarged abdominal mass after receiving a booster dose of the COVID-19 mRNA vaccine. This mass occupied the retroperitoneal space, infiltrated the psoas muscle, and resulted in ureteric compression and hydronephrosis. Percutaneous drainage and analysis of the perirenal fluid revealed the presence of lymphatic fluid. In summary, lymphadenopathy is a recognized adverse reaction to the Pfizer and Moderna vaccines. Patients with compromised immune systems should be informed about the incidence and potential severity of lymphadenopathy following booster vaccination.